Discussing the Principles of Symbolism Approach and Their Effectiveness in Finding the Meaning of Quranic Symbols - Abdulqayum Tayeb; Habiburrahman Rizapoor (CV. AFDIFAL MAJU BERKAH, 2025)
Symbolism is one of the significant literary approaches through which various literary, ideological, and scientific texts are analyzed using its concepts. In this study, the symbolic verses of the Holy Quran are interpreted based on the foundational principles of this approach. The primary aim of this work is to determine the extent of symbolism in the Quranic verses and to understand the various viewpoints regarding the